Thioamide modified polymer sphere, preparation thereof and application of thioamide modified polymer sphere in adsorption and recovery of gold
The self-porous microporous polymer ball adsorbent modified by thioamide solves the problem of insufficient stability and capacity of traditional adsorbents, and efficient recycling of gold in electronic waste is achieved, with good stability and selectivity. Suitable for recycling of precious metals.
Patent Information
- Application Number
- CN202411341066.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional adsorbents have poor stability in solution and have low adsorption capacity, making it difficult to efficiently recover precious metals such as gold from electronic waste.
The spherical adsorbent is prepared by phase conversion method by using thioamide-modified self-porous microporous polymer spheres, and the diameter and structure of the spherical adsorption kinetics are controlled, and the adsorption ability to noble metals is enhanced through thioamide modification.
It has achieved efficient capture of Au ions in the solution, has high adsorption capacity and selectivity, can maintain stability under different pH conditions, and can directly calcinate to obtain gold nanoparticles, significantly improving the recycling efficiency of precious metals.
Smart Images

Figure BDA0005059708320000021 
Figure FDA0005059708310000011 
Figure HDA0005059708330000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental engineering precious metal adsorption recovery, and particularly relates to a thioamide-modified polymer ball and its preparation and application in gold adsorption recovery. Background Art
[0002] Gold is one of the rarest and most precious metals. It is widely used in aerospace, medical and electronic products due to its unique antioxidant, corrosion resistance and good electrical conductivity. With the rise of the computer industry, the rapid development of electronic equipment has led to an urgent increase in the demand for gold. As a non-renewable resource, the concentration of gold in the earth's crust is low, far lower than the gold content in electronic equipment. More importantly, due to the frequent damage of electronic equipment and their increasingly rapid replacement, a large amount of electronic waste is generated, which will pose a potential threat to the environment if discarded at will. Therefore, in order to meet the growing demand for gold, it is necessary and very valuable to adsorb and recover gold (Au) from electronic waste leachate.
[0003] Adsorption is considered to be a reliable method for separating Au from solution due to its advantages such as simple process, low energy consumption, low cost and high efficiency. Compared with traditional methods such as solvent extraction, chemical precipitation and ion exchange, adsorption also has the characteristics of fast speed and large capacity. Traditional adsorbents such as activated carbon, resin and MOFs have defects such as poor continuous water stability in solution. Therefore, how to overcome the problems of poor stability and low adsorption capacity of traditional adsorbents has become a problem that this field is committed to solving. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems of poor stability and low adsorption capacity of traditional adsorbents, and to provide a thioamide-modified polymer sphere adsorbent and a preparation method and application thereof.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0006] A thioamide-modified polymer ball, the structural formula of the polymer is as follows:
[0007]
[0008] Furthermore, the average diameter of the polymer balls is 0.7-1.2 mm, preferably controlled at about 1 mm.
[0009] The organic polymer ball adsorbent of the present invention can achieve good adsorption kinetics effect and reach an ideal adsorption capacity by modifying the groups and controlling the diameter of the adsorption balls.
[0010] The present invention further provides a method for preparing the thioamide-modified polymer spheres, wherein the self-polymerizing microporous polymer TPIM-1 is dissolved in a solution of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF) or N-methylpyrrolidone (NMP), and the solution is dripped into an aqueous solution of methanol or ethanol to obtain the polymer spheres by a phase inversion method.
[0011] The thioamide-modified self-polymerized microporous polymer (TPIM-1) is stirred and fully dissolved in a solvent such as N,N-dimethylformamide (DMF); further, bubbles in the solution can be removed by ultrasound.
[0012] Furthermore, the mass volume ratio of the self-polymerized microporous polymer to the solvent is 5-6:100, and the volume ratio of methanol or ethanol to water is 10:0 to 0:10, preferably 1:9-3:7.
[0013] The solvent is preferably DMF, and the solution of the self-polymerizing microporous polymer is dripped into an ethanol aqueous solution. After the phase inversion, the spherical shape of the particles is more uniform.
[0014] Furthermore, the mass volume ratio of the self-polymerized microporous polymer to DMF is 5.5:100, and the volume ratio of ethanol to water is 2:8.
[0015] Specifically, a syringe may be used to drop the polymer solution into a methanol or ethanol aqueous solution.
[0016] Preferably, the dripping rate of the polymer solution when dripping into the aqueous solution is 0.5-2 mL / min, preferably 0.5 mL / min.
[0017] The distance between the dropping position of the polymer solution and the liquid surface of the aqueous solution is 8-15 cm, preferably 12 cm.
[0018] The falling path of the polymer solution after being dropped into the aqueous solution is not less than 30 cm. The polymer solution will immediately form a ball after being dropped into the aqueous solution of ethanol. In order to ensure that the phase transformation inside the droplet is fully completed, the falling path must be long.
[0019] The organic polymer spherical adsorbent obtained by phase inversion is washed with deionized water and then stored in deionized water for later use.
[0020] The obtained spherical adsorbent has an average size of 1 mm and can maintain structural stability in aqueous solutions with different pH conditions of 1 to 12.
[0021] The entire preparation process will affect the shape, size and internal structure of the polymer spheres, thereby affecting the adsorption kinetics of the polymer spheres.
[0022] The thioamide-modified polymer spheres are well applied in the adsorption of precious metals such as Pd, Au, etc., especially Au, and can efficiently capture Au ions in the solution to achieve the recycling of precious metal resources.
[0023] The polymer spheres of the present invention are used to treat simulated electronic waste liquid with an Au concentration of 10.57 mg / L, a Ni concentration of 84.16 mg / L, and a Cu concentration of 966.2 mg / L. The mixture is shaken in a shaker at room temperature for 12 hours. The maximum adsorption capacity of Au is 18.26 mg / g, and the selectivity coefficients relative to Ni and Cu are 231.86 and 205.25, respectively.
[0024] After the thioamide-based self-polymerized microporous polymer ball adsorbent of the present invention adsorbs Au ions, it can be directly calcined in the air to obtain gold nanoparticles.
[0025] The thioamide-based self-polymerizing microporous polymer TPIM-1 of the present invention can be prepared by a simple reflux reaction, that is, by dissolving the polymer material PIM-1 in 1,4-dioxane and mixing with phosphorus pentasulfide (P2S5) and sodium sulfite (Na2SO3).
[0026] The preparation method of the self-polymerized microporous polymer PIM before modification can refer to the following method but is not limited to the following method: under a nitrogen atmosphere, 5.106g of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane (TTSBI), 3g of tetrafluoroterephthalonitrile (TFTPN) and 6.21g of potassium carbonate are dissolved in 30mL of DMAC, and reacted at 150°C for 30min to obtain a viscous solution. After the reaction is completed, it is poured into a methanol solution for solidification to produce a bright yellow solid. The solid is purified and placed in a vacuum drying oven at 80°C for 12h to obtain a PIM polymer.
[0027] The adsorption material used in the present invention is obtained by modifying the self-polymerized microporous polymer PIM-1 by thioamide to obtain TPIM-1, so that it has amino and sulfur functional groups with specific adsorption effects on Au, and further prepares a spherical porous material by phase transformation. The adsorption material has a high specific surface area, good thermal stability and water stability, and a large number of functional groups with strong binding ability to Au ions, and has a high adsorption capacity and adsorption selectivity. Even in a low-concentration Au solution, it still maintains a good adsorption effect, and has a good application prospect and practicality for gold recovery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The preparation of the TPIM-1 polymer ball adsorbent of the present invention and its actual schematic diagram;
[0029] Figure 2This is a scanning electron microscope image of the cross section of the TPIM-1 polymer ball adsorbent in Example 1 of the present invention;
[0030] Figure 3 This is the N2 adsorption curve of the TPIM-1 polymer ball adsorbent in Example 1 of the present invention;
[0031] Figure 4 This is an infrared image of the TPIM-1 polymer ball adsorbent in Example 1 of the present invention;
[0032] Figure 5 This is a graph showing the removal rate of the TPIM-1 polymer ball adsorbent at different pH values in Experimental Example 1 of the present invention;
[0033] Figure 6 This is the adsorption kinetics diagram of the TPIM-1 polymer ball adsorbent of Experimental Example 2 of the present invention;
[0034] Figure 7 is the adsorption isotherm diagram of the TPIM-1 polymer ball adsorbent of Experimental Example 3 of the present invention;
[0035] Figure 8 This is a selective adsorption diagram of the TPIM-1 polymer ball adsorbent of Experimental Example 4 of the present invention;
[0036] Fig. 9 This is a graph showing the adsorption performance of the TPIM-1 polymer ball adsorbent of Experimental Example 5 of the present invention in a simulated electronic waste leachate. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto: Embodiment 1
[0038] Synthesis steps of thioamide modified self-polymerized microporous polymer TPIM-1 ball adsorbent:
[0039] 1) Under nitrogen atmosphere, first add 5.106g monomer 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane (TTSBI) and 30mL N,N-dimethylacetamide (DMAC) into a 250mL three-necked flask, stir and dissolve, then add 3.001g tetrafluoroterephthalonitrile (TFTPN), at this time the solution turns bright red, after TFTPN is completely dissolved, add 6.21g potassium carbonate powder, the solution quickly turns yellow and viscous, transfer the three-necked flask to a 150℃ oil bath and react for 30min. After the reaction is completed, pour the yellow solution into methanol to solidify to obtain a fluorescent yellow solid. After the solid is purified, it is vacuum dried at 80℃ for 12h to obtain the self-polymerized microporous polymer PIM-1.
[0040] 2) First, 7.72g of phosphorus pentasulfide and 2.19g of sodium sulfite powder were added to a single-necked flask, 20mL of ethanol was poured in and stirred continuously at room temperature for 1 hour, during which hydrogen sulfide gas was generated. Then 2g of PIM-1 powder was weighed and added to a single-necked flask and 200mL of 1,4-dioxane solvent was poured in, the reaction was heated to 80°C in an oil bath and refluxed and stirred for 20 hours, then 200mL of water was added when the reactant was cooled to room temperature and stirred for 4 hours, during which a yellow precipitate was generated. After the reaction was completed, the yellow precipitate was collected and washed with chloroform and methanol to completely remove the by-products and impurities produced by the reaction. Finally, the powder was collected and dissolved in tetrahydrofuran (THF), and then precipitated in methanol again, and the obtained precipitate was vacuum dried at 90°C for 12 hours to obtain orange powder TPIM-1.
[0041] TPIM-1 is not limited to the above-mentioned method, and any known preparation method is also possible.
[0042] 3) Take 300 mg of TPIM-1 powder and dissolve it in 3 mL, 5 mL and 7 mL of anhydrous N, N-dimethylformamide (DMF) solution respectively. After complete dissolution, use an ultrasonic machine to remove bubbles. Then, the solution is drawn out with a syringe and dripped into a mixed solution of ethanol / water (volume ratio is 1:4) drop by drop at a rate of 0.5 mL / min through a syringe pump. The liquid level between the syringe and the ethanol / water mixed solution is 12 cm, and the falling path of the solution after dripping into the ethanol-water solution is 30 cm. The liquid droplets on the liquid surface quickly undergo phase transformation in the ethanol / water mixed solution and become spherical structures. Among them, the sample with 3 mL of DMF has a larger ball size due to its high viscosity. The ball shape formed by the sample with 5 mL of DMF is relatively regular. The sample with 7 mL of DMF is relatively dilute, resulting in different ball shapes, and even tailing. After all the drops are finished, the TPIM-1 polymer balls are washed several times and finally transferred to deionized water for storage for subsequent use. The internal morphology and structure of the TPIM-1 polymer ball adsorbent can be seen in Figure 2 , nitrogen adsorption and desorption curves are shown in Figure 3 , infrared image see Figure 4 .
[0043] Adsorption performance test
[0044] The Au ion solutions used in the adsorption experiments were all prepared with deionized water, the pH of the solution was 1-10, the concentration was 100-1000 mg / L, the amount of solution and the amount of adsorbent were 20 mL and 10 mg respectively, the adsorption temperature was 25°C, and the adsorption time was 30-720 min.
[0045] Experimental Example 1
[0046] 10 mg of TPIM-1 polymer ball adsorbent was weighed and placed in an Au ion solution with an initial concentration of 100 mg / L at pH = 1-10, and stirred at 25°C for 12 hours. The concentration of Au ions in each sample was measured using an inductively coupled plasma optical emission spectrometer (ICP-OES). Among them, under all pH conditions tested, the removal rate was greater than 95%. The adsorption performance is shown in Figure 2. Figure 5 shown.
[0047] Experimental Example 2
[0048] Weigh 10 mg of TPIM-1 polymer ball adsorbent and place it in an Au ion solution with an initial concentration of 100 mg / L at pH 5. Samples were taken at different time periods between 30 and 720 min at 25°C, and the Au ion concentration was measured using an inductively coupled plasma optical emission spectrometer (ICP-OES). As the time extended from 30 min to 720 min, the adsorption amount increased from 135.20 mg / g to 199.43 mg / g, and the removal rate reached more than 99.7%, but it basically reached 199.22 mg / g at 240 min. The adsorption curve is shown in Figure 2. Figure 6 shown.
[0049] Experimental Example 3
[0050] 10 mg of TPIM-1 polymer ball adsorbent was weighed and placed in an Au ion solution with an initial concentration of 100-1000 mg / L at pH = 5. The mixture was stirred at 15°C-45°C for 12 hours. The concentration of Au ions in each sample was measured using an inductively coupled plasma optical emission spectrometer (ICP-OES). When the temperature was 45°C, the maximum adsorption capacity of the adsorbent was 1872.8 mg / g. The adsorption performance is shown in Figure 2. Figure 7 shown.
[0051] Experimental Example 4
[0052] Weigh 10 mg of TPIM-1 polymer spherical adsorbent and put it into a mixed metal ion solution with a pH of 5, in which the Au ion concentration is 10 mg / L and the coexisting cadmium, copper, lead, nickel, and zinc ion concentrations are 100 mg / L. Stir for 12 hours at 25°C. The concentration of Au ions in each sample was measured using an inductively coupled plasma optical emission spectrometer (ICP-OES). Even if the initial concentration of the coexisting ions is 10 times greater than that of Au, the TPIM-1 polymer spherical adsorbent can still remove more than 90% of the Au ions. The adsorption performance is shown in Figure 2. Figure 8 shown.
[0053] Experimental Example 5
[0054] Weigh 10 mg of TPIM-1 polymer ball adsorbent and place it in a simulated electronic waste leachate. The main ions are copper ions (966.2 mg / L), nickel ions (84.16 mg / L) and Au ions (10.57 mg / L). Stir for 12 hours at 25°C, and use an inductively coupled plasma optical emission spectrometer (ICP-OES) to measure the concentration of each Au metal ion in the sample. In the electronic waste leachate, the TPIM-1 polymer ball adsorbent still has an Au ion removal efficiency of more than 80%, and the Au ion concentration is reduced from 10.57 mg / L to 1.44 mg / L. The adsorption performance is as follows Fig. 9 shown.
Claims
1. A thioamide-modified polymer ball, characterized in that: The structural formula of the polymer is shown below:
2. The thioamide-modified polymer sphere according to claim 1, characterized in that: The average diameter of the polymer spheres was 1 mm.
3. The method for preparing the thioamide-modified polymer spheres according to claim 1, characterized in that: The self-polymerized microporous polymer TPIM-1 was dissolved in a solution of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF) or N-methylpyrrolidone (NMP), and then dropped into an aqueous solution of methanol or ethanol to prepare polymer spheres by a phase inversion method.
4. The method for preparing thioamide-modified polymer spheres according to claim 3, characterized in that: The mass volume ratio of the self-polymerized microporous polymer to the solvent is 5-6:100, and the volume ratio of methanol or ethanol to water is 10:0-0:
10.
5. The method for preparing thioamide-modified polymer spheres according to claim 4, characterized in that: The solvent is DMF, and the solution of the self-polymerized microporous polymer is dropped into an aqueous solution of ethanol.
6. The method for preparing thioamide-modified polymer spheres according to claim 5, characterized in that: The mass volume ratio of the self-polymerized microporous polymer to DMF was 5.5:100, and the volume ratio of ethanol to water was 2:
8.
7. The method for preparing thioamide-modified polymer spheres according to any one of claims 3 to 6, characterized in that: The polymer solution is dripped into the methanol or ethanol aqueous solution at a dripping rate of 0.5-2 mL / min.
8. The method for preparing thioamide-modified polymer spheres according to claim 7, characterized in that: The distance between the dropping position of the polymer solution and the liquid surface of the aqueous solution is 8-15 cm.
9. The method for preparing thioamide-modified polymer spheres according to claim 8, characterized in that: The falling path of the polymer solution after being dropped into the aqueous solution is not less than 30 cm.
10. Use of the thioamide-modified polymer spheres according to claim 1 in adsorbing Au.
Citation Information
Patent Citations
Method for preparing thioamide-based chelating nanofiber for adsorbing heavy metal ions
CN102140705A
Method for enrichment recycling solid gold from gold-bearing solution
CN110643828A
Modified polymer adsorbent for selectively adsorbing and recycling precious metal ions and preparation method ofmodified polymer adsorbent
CN113145082A
Polymer-based porous ball material as well as preparation method and application thereof
CN116970211A